2011
DOI: 10.1063/1.3564882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-pressure oxygen annealing on negative bias illumination stress-induced instability of InGaZnO thin film transistors

Abstract: Negative-bias illumination stress (NBIS) of amorphous InGaZnO (IGZO) transistors can cause a large negative shift (>7.1 V) in threshold voltage, something frequently attributed to the trapping of photoinduced hole carriers. This work demonstrates that the deterioration of threshold voltage by NBIS can be strongly suppressed by high-pressure annealing under 10 atm O2 ambient. This improvement occurred through a reduction in oxygen vacancy defects in the IGZO film, indicating that a photoinduced transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
140
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(142 citation statements)
references
References 18 publications
1
140
1
Order By: Relevance
“…45 The tail states or undercoordinated cations are intrinsic to the amorphous phase, and hence difficult to suppress unless the material composition is changed. One viable approach would be to increase the optical gap by increasing the atomic density of the amorphous film through compressive strain or dopants.…”
mentioning
confidence: 99%
“…45 The tail states or undercoordinated cations are intrinsic to the amorphous phase, and hence difficult to suppress unless the material composition is changed. One viable approach would be to increase the optical gap by increasing the atomic density of the amorphous film through compressive strain or dopants.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] However, there are still many issues related to the control of threshold voltage and bias-induced degradation. [6][7][8][9][10][11] Therefore, there have been many studies on improving AOS TFT stability such as high-pressure oxygen annealing, 12 annealing in hydrogen environment, 13 O 2 plasma treatment, 14 suitable passivation materials, 15 long channel TFT 16 and long-time annealing, etc. 17 Especially, the performance of a-IGZO TFT depends on channel length, and the TFTs with channel length less than 2 µm exhibit mostly depletion mode behavior.…”
mentioning
confidence: 99%
“…In addition, low-permeable passivation layers (such as Al 2 O 3 and SiON x ) resulted in better device stability, even under stress conditions [159]. Furthermore, it was revealed that robust oxide semiconductors normally contain higher oxygen content during the deposition process and post treatment [160,161]. In summary, in terms of materials and structures, stable and reliable oxide TFTs have less hydrogen and higher oxygen composition to suppress V th shifts when exposed to the four practical stress conditions.…”
Section: Stable and Reliable Oxide Tftsmentioning
confidence: 99%
“…In order to improve the stability of oxide TFTs, researchers have suggested various methods including optimized structures [82], suitable gate insulator materials [158], impermeable passivation layers [159], robust semiconductors [160] 3)BZN(0.7) (a) (b) (c) Fig. 18 (a) and post-annealing treatments [161]. For instance, by comparing bottom-gate TFTs with a back-channel-etch (BCE) or an etch-stop (ES) structure, researchers found that the stability of an ES-type device was superior to that of a BCE type device, which may be attributable to the formation of defective interfacial layers [82].…”
Section: Stable and Reliable Oxide Tftsmentioning
confidence: 99%